PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK GERAK KELAS VII SMP NEGERI PADANGSIDIMPUAN - Siregar, Dwi Aninditya (Jurnal Physics Education (PhysEdu), 2023)
This research aims to find out whether there is influence of students’ facilitator and explaining to the students’ achievement in movement of the VII grade students’ of SMP Negeri 3 Padangsidimpuan. This research is doneby using experiment method. The population of this research is all of VII grade students’ of SMP Negeri 3 Padangsidimpuan, consists of 290 students’. Sample of this research is 35 students’, taken by using cluster sampling. The data of this research is processed by two step. The first, by experiment analysis, to see the influence of both variables, namely students’ facilitator and explaining to the students’ achievement in movement. The second, by inferential analysis, to test the hypothesis, by using t test. Based on the calculation, the mean of students’ facilitator and explaining is 3.2. It is very good category. Then the students’ achievement in movement before the application of students’ facilitator and explaining is 70. It is good category and the students’ achievement in movement after the application of students’ facilitator and explaining is 75, it is good category. Based on the calculation in inferential analysis, it is found that t count is 2.25 and if it is compared to t table in 5% significant, it is found 1.675. After comparing t count and t table, it is got that t count is greater than t table (2.25 > 1.675). The hypothesis is accepted. Means that there is significant influence of students’ facilitator and explaining to the students’ achievement in movement of the VII grade students’ of SMPNegeri 3 Padangsidimpuan.